Highly Plasmonic Titanium Nitride by Room-Temperature Sputtering - Chang, Chun-Chieh; Nogan, John; Yang, Zu-Po; Kort-Kamp, Wilton J. M.; Ross, Willard; Luk, Ting S.; Dalvit, Diego A. R.; Azad, Abul K.; Chen, Hou-Tong (Scientific reports, 2019)
Titanium nitride (TiN) has recently emerged as an attractive alternative material for plasmonics. However, the typical high-temperature deposition of plasmonic TiN using either sputtering or atomic layer deposition has greatly limited its potential applications and prevented its integration into existing CMOS device architectures. Here, we demonstrate highly plasmonic TiN thin films and nanostructures by a room-temperature, low-power, and bias-free reactive sputtering process. We investigate the optical properties of the TiN films and their dependence on the sputtering conditions and substrate materials. We find that our TiN possesses one of the largest negative values of the real part of the dielectric function as compared to all other plasmonic TiN films reported to date. Two-dimensional periodic arrays of TiN nanodisks are then fabricated, from which we validate that strong plasmonic resonances are supported. Our room-temperature deposition process can allow for fabricating complex plasmonic TiN nanostructures and be integrated into the fabrication of existing CMOS-based photonic devices to enhance their performance and functionalities.